Trends in Oropharyngeal Cancer Incidence Among Adult Men and Women in the United States From 2001 to 2018 - Guo, Fangjian; Chang, Mihyun; Scholl, Matthew; McKinnon, Brian; Berenson, Abbey B. (Frontiers in Oncology, 2022)
Background The human papillomavirus (HPV) vaccine was approved in 2006 and has been shown to decrease vaccine-related HPV types in the oropharynx. Its impact on the incidence of HPV-related oropharyngeal squamous cell carcinoma (OPSCC) has not been examined. We investigated the impact of HPV vaccination on the incidence of HPV-related OPSCC in the US among male and female adults from different age groups. Methods The US Cancer Statistics 2001–2018 database and the National Cancer Institute (NCI)’s Surveillance Epidemiology and End Results (SEER) program were used in this study. OPSCC incidence was age-adjusted to the US standard population in 2000. Cause-specific 5-year survival probability was calculated using 60 monthly intervals in SEER*Stat software. Results Incidence of HPV-related OPSCC was much higher in males than in females. Age-adjusted annual incidence of OPSCC was significantly lower in 2014-2018 than in 2002-2006 among males 20-44 years old (11.4 vs 12.8 per 1,000,000, rate ratio 0.89, 95% confidence interval 0.84-0.93) and among females 20-44 years old (3.0 vs 3.6 per 1,000,000, rate ratio 0.86, 95% confidence interval 0.78-0.95), but increased in both 45-64 year old and 65+ year old males and females. Joinpoint regression revealed a significant joint in the HPV-OPSCC incidence trend for 20-44-year-old males in 2008 at which time the incidence began to decrease. Except for 20-44 year old females (74.8% in 2002-2006 vs. 75.7% in 2009-2013, p=0.84), cancer-specific 5-year survivals significantly improved for males and females of all age groups. Conclusions HPV-related OPSCC was much more common in males. Incidence of HPV-related OPSCC declined among young adults during the vaccination era compared with pre-vaccination era. Cancer-specific 5-year survival was significantly improved in young males but not in young females.